Keterkaitan Makna Simbol Cover Single Terhadap Lirik Lagu Fadeless Pada Band The Gazette (Kajian Semantik) - Rahayu Dewi, Made; Yuliani Giri, Ni Luh Kade; Andry Anita Dewi, Ni Made (Humanis, 2016)
This research entitled “Linkage Meaning Symbol of Cover Single from Lyric Fadeless on the GazettE Band”. The data was analyzed by the literature method and descriptive analysis. This study used the semantic theory by Abdul Chaer (2009), semiotic theory by Marcel Danesi (2012), and the triangular semiotic theory by Odgen & Richard (2009). The aims of this study are to know the meaning and relationship of symbol in the cover single and the lyric of Fadeless by the GazettE band. Based on the data analysis, there were eight symbols meaning that appeared in the cover single of Fadeless and the meaning in the song lyric Fadeless, including ten datas connotative meaning, one data of the term meaning, eight datas conceptual meaning, four datas of metaphor meaning. Meanwhile, there were eight parts which had relationship between the cover single and the song lyric of Fadeless.